2010
DOI: 10.1007/s10165-010-0372-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased level of heme oxygenase-1 in rheumatoid arthritis synovial fluid

Abstract: We investigated the expression and localization of heme oxygenase-1 (HO-1) in synovial fluid and synovial tissue, and examined the stimulation of HO-1 production in rheumatoid synovial fibroblasts (RASFs). Synovial fluid samples were obtained from knee joints of 20 rheumatoid arthritis (RA) and 20 osteoarthritis (OA) patients, and concentration of HO-1 and matrix metalloproteinase-3 (MMP-3) were measured by enzyme-linked immunosorbent assay (ELISA). Synovial tissues obtained from RA or OA patients during total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
(38 reference statements)
0
14
2
Order By: Relevance
“…None of serum levels of HO-1, BMP-7, and Runx2 was associated with inflammatory markers or disease activity in any of the patient groups under investigation. In contrast to our data, Kitamura et al found that HO-1 levels in RA synovial fluids correlated with serum levels of CRP [ 4 ]. A previous study on either RA or OA revealed that HO-1 significantly reduced the production of proinflammatory cytokines [ 4 , 9 , 13 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…None of serum levels of HO-1, BMP-7, and Runx2 was associated with inflammatory markers or disease activity in any of the patient groups under investigation. In contrast to our data, Kitamura et al found that HO-1 levels in RA synovial fluids correlated with serum levels of CRP [ 4 ]. A previous study on either RA or OA revealed that HO-1 significantly reduced the production of proinflammatory cytokines [ 4 , 9 , 13 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our data, Kitamura et al found that HO-1 levels in RA synovial fluids correlated with serum levels of CRP [ 4 ]. A previous study on either RA or OA revealed that HO-1 significantly reduced the production of proinflammatory cytokines [ 4 , 9 , 13 ]. In line with our results, Korkosz et al found no correlation between the serum BMP-7 concentrations and either ESR or CRP in patients with AS [ 34 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…An association of HO-1 promoter polymorphism with rheumatoid arthritis (RA) has been reported [4] and patients with the SS genotype, resulting in a higher HO-1 expression, may have a better long-term radiographic outcome despite disease activity [5]. HO-1 protein is expressed in synovial tissues of RA patients [6] and its presence in synovial fluid may be a marker of joint inflammation [7] Nevertheless, treatment of RA patients with tumor necrosis factor α (TNF-α) antagonists may block the TNF-α-dependent suppression of HO-1 expression in peripheral blood cells, resulting in amelioration of inflammation [8].…”
Section: Introductionmentioning
confidence: 99%
“…HO-1 exhibits multiple beneficial properties including antioxidant, anti-inflammatory and cytoprotective functions and is often endogenously induced by various stress stimuli 18,19,43,44 . It has been detected in human OA synovium, cartilage and synovial fluids 42e44 .…”
Section: Discussionmentioning
confidence: 99%